GROWTH AND YIELD OF BEETROOT (Beta vulgaris L) AS INFLUENCED BY GOAT MANURE AND SUGARCANE MOLASSES WITH HALF DOSAGE OF PHOSPHORUS INORGANIC FERTILIZER - Priyadarshani, W.M.Nadeeka; Seran, Thayamini (Journal of Agricultural Sciences (Belgrade), 2020)
The pot experiment was conducted to study the effect of goat manure and sugarcane molasses on growth and yield of beetroot (Beta vulgaris L.) in sandy regosol. The experiment was laid out in a completely randomized design (CRD) with six treatments. The treatments included inorganic fertilizer (T1), 10 t/ha goat manure alone (T2) and also 10 t/ha goat manure and 50% triple super phosphate (TSP) with 1-4 t/ha sugarcane molasses (T3-T6). The results showed that plant growth parameters (leaf length, leaf petiole length, leaf width, leaf number, fresh weight and dry weight of leaves) were significantly varied among the treatments. And also there was significant difference in diameter of beetroot among the treatments. Significant differences (P
Keywords: beetroot, goat manure, molasses, radish, yield